Reviewing Various Obstacles in Implementing the Independent Curriculum in Junior High Schools - Nur Halifah Rahmawati; Vera Dewi Susanti; Tias Nur Aini; Tri Nurvita Sari; Laura Ikhsa Andriani (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2024)
Curriculum development is one of the systemic changes that can improve and support learning. The Merdeka Curriculum is one of the Ministry of Education and Culture's efforts to overcome learning loss due to the long pandemic that hampered the education process. The Independent Curriculum allows every student to develop according to their individual needs and potential. Assuming that there are various policies in both the old and new curriculum, this is one thing that is not explained enough. Therefore, this research aims to analyze the challenges teachers face in implementing the Independent Curriculum. This research uses document analysis methods. The findings of this study indicate a high workload due to work and a lack of ongoing training. Apart from that, teachers also have difficulty encouraging students to learn. This study concludes that increasing teacher capacity through structured and ongoing training programs is very important to support the successful implementation of the Merdeka Curriculum.